2015
DOI: 10.1002/bkcs.10483
|View full text |Cite
|
Sign up to set email alerts
|

N‐Capping Effects of Stapled Heptapeptides on Antimicrobial and Hemolytic Activities

Abstract: In our previous study, we showcased the potential of an all‐hydrocarbon stapled heptapeptide as a privileged scaffold for the design of artificial antimicrobial peptides. We demonstrated that the amphipathic helicity and the subtle balance between hydrophobicity and hydrophilicity are important structural features for the antimicrobial activities of this class of antimicrobial agents. In this study, we show that elimination of the N‐acetyl cap can further improve the pharmacological properties of the most pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Only in the case of S3, deacetylation proved to be an advantageous modification. The deacetylated analog maintained helicity, exhibited greater antimicrobial activity, and even lowered hemolysis [ 38 ].…”
Section: Hydrocarbon Stapled Antimicrobial Peptidesmentioning
confidence: 99%
“…Only in the case of S3, deacetylation proved to be an advantageous modification. The deacetylated analog maintained helicity, exhibited greater antimicrobial activity, and even lowered hemolysis [ 38 ].…”
Section: Hydrocarbon Stapled Antimicrobial Peptidesmentioning
confidence: 99%
“…This de novo designed heptapeptide showed moderate antimicrobial activity against various bacterial species in our previous study. In a follow‐up study, we have also demonstrated that its analog, that bore a free amino group at the N ‐terminus, displayed a one to four‐fold increase in antimicrobial activity depending on the bacterial species …”
Section: Resultsmentioning
confidence: 99%
“…Many of these cationic AMPs require an amphipathic helical conformation for antimicrobial activity . Therefore, using Verdine's all‐hydrocarbon peptide stapling system, our laboratory has previously developed a series of short synthetic AMPs, consisting of seven amino acid residues . Although these short amphipathic helices of “stapled” heptapeptides did not cause any detectable hemolysis on human red blood cells, they only showed moderate antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the acetylation of N-terminal would increase the helical content and peptide stability, however, it also reduces the total net positive charge of AMPs. Therefore, though this modification showed effect on higher perturbation in the case of mastoparan-like peptide [ 179 ], it is not always good for biological activity as demonstrated in the case of stapled peptides [ 161 , 180 ]. Regarding C-terminal, amidation of its carboxyl group was proven to be a good strategy to prevent metabolic degradation and improve antimicrobial potency [ 6 , [181] , [182] , [183] ].…”
Section: Approaches To Improve Biological Activities Of Ampsmentioning
confidence: 99%